2020
DOI: 10.1016/j.tmaid.2020.101909
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptoms from exposure to Covid-19 provide support to clinical diagnosis, triage and prognosis: An exploratory analysis

Abstract: Background Symptomatic COVID-19 is prevalent in the community. We identify factors indicating COVID-19 positivity in non-hospitalized patients and prognosticators of moderate-to-severe disease. Methods Appeals conducted in April-June 2020 in social media, collaborating medical societies and patient advocacy groups recruited 20,476 participants ≥18 years who believed they had COVID-19 exposure. Volunteers consented on-line and reported height, weight, concomitant illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 16 publications
5
23
0
Order By: Relevance
“…The results also show that all the symptom frequencies reported here (with the exception of rhinorrhea and sneezing) are different between C19+ from C19-users. This agrees with other studies [10] [11] that also reported hyposmia, dysgeusia and fever as significantly increased in C19+ persons. Considering the high relative difference of hyposmia and dysgeusia frequencies for C19+ users, our study suggests that hyposmia and dysgeusia are specific but not sensitive, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The results also show that all the symptom frequencies reported here (with the exception of rhinorrhea and sneezing) are different between C19+ from C19-users. This agrees with other studies [10] [11] that also reported hyposmia, dysgeusia and fever as significantly increased in C19+ persons. Considering the high relative difference of hyposmia and dysgeusia frequencies for C19+ users, our study suggests that hyposmia and dysgeusia are specific but not sensitive, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, anosmia or dysgeusia may even be regarded as a highly reliable diagnostic marker in very mild cases, as also proposed by other colleagues. 23,24 Of note, we could not find a correlation between the number of symptoms (implying severity) and the level of the neutralisation titre as supported by other recently published data. 25,26 Our data further indicate that in individuals with anosmia/dysgeusia as a sole symptom, the quality and quantity of neutralising/protective antibodies does not differ compared to those with several reported and typical COVID-19 symptoms (fever, cough, dyspnoea).…”
Section: Discussionsupporting
confidence: 85%
“…Participants who reported testing positive for COVID-19 within the 14 days preceding enrollment (n=1,518; median [IQR]=7 [4][5][6][7][8][9] days) included 70 (4.6%) individuals who reported taking medication for an autoimmune condition. Participants taking medication for an autoimmune condition were on average older (mean age 46.9 vs 40.9 years), less likely to be Hispanic or Latino (7% vs 16%), and more likely to be female (93% vs 87%) and to report other comorbidities compared to all other participants (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Participants reporting use of medications for autoimmune disease reported a median [IQR] of 7 [5][6][7][8][9] symptoms at enrollment, while the median [IQR] number of symptoms for all other participants was 7 [4][5][6][7][8][9]. The median [IQR] severity score at enrollment for those reporting use of medications for autoimmune disease was 12 [7][8][9][10][11][12][13][14][15][16][17] decreased sense of smell or taste at enrollment; among those reporting use of medications for autoimmune disease, a higher proportion reported symptoms at all time points in follow-up, as well as symptoms of greater severity (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation